2010
DOI: 10.1111/j.1540-8183.2010.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Outcome in Female Patients Undergoing Endovascular Intervention

Abstract: Our study is the first of its kind to specify predictors of poor outcomes after EI in female patients with symptomatic PAD. The strongest predictors of subsequent EI and TVR, limb loss, and vascular surgery, as well as death, were found to be chronic kidney disease (CKD; PRE-CR > 1.5 mg/dL), decreased BMI, Rutherford class, and anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Percutaneous methods are preferred, but outcomes are worse among patients with higher rates of repeat percutaneous angioplasty, subsequent surgical revascularization, or limb loss and death. 166 In another retrospective analysis, CKD 5D patients who underwent percutaneous compared with surgical revascularization experienced higher limb salvage rates. 167 Perioperative morbidity and mortality are high among CKD patients undergoing these procedures.…”
Section: Peripheral Arterial Diseasementioning
confidence: 97%
“…Percutaneous methods are preferred, but outcomes are worse among patients with higher rates of repeat percutaneous angioplasty, subsequent surgical revascularization, or limb loss and death. 166 In another retrospective analysis, CKD 5D patients who underwent percutaneous compared with surgical revascularization experienced higher limb salvage rates. 167 Perioperative morbidity and mortality are high among CKD patients undergoing these procedures.…”
Section: Peripheral Arterial Diseasementioning
confidence: 97%
“…9,19,20 Additionally, it has recently been shown that anemia predicts mortality following surgery for colorectal cancer, endovascular intervention for peripheral arterial disease, open vascular reconstruction, and coronary artery bypass grafting. 21 23 In fact, a recent study has suggested that the presence and severity of preoperative anemia in vascular patients are significant predictors of 30-day and 5-year cardiac events, regardless of underlying heart failure or renal disease. 24 The morbidity and mortality observed in this current series cannot be directly linked to technical issues associated with EVAR, as none of these patients had a proven migration, endoleak, or other significant device-related complication.…”
Section: Discussionmentioning
confidence: 99%
“… Kuijk et al (2011) [ 147 ] Prevalence of obesity and association on long-term survival; medical treatment at time of discharge and obesity and long-term survival 2,933 6 years ABI < 0.9 or a history of IC with a previous intervention Underweight was an independent predictor of mortality, while overweight protected for all-cause mortality. Abbas et al (2010) [ 124 ] Predictors of poor outcomes in female patients undergoing EI for symptomatic PAD. 292 ~ 2 years Patients who underwent EI Low BMI predicted poor outcomes (subsequent EI and TVR, limb loss, and vascular surgery, death) Kumakura et al (2010) [ 117 ] Long-term survival in patients with PAD and severity of symptoms and association to CKD, and BMI 652 15 years IC or CLI Low BMI was a significant risk factor for mortality Galal et al (2008) [ 116 ] Influence of COPD on the relationship between BMI and mortality in patients with PAD 2,392 4.37 years Vascular surgical interventions (abdominal aortic surgery, carotid endarterectomy), or lower limb arterial revascularization procedures.…”
Section: Impact Of Obesity or Underweight Status On Disease Progressi...mentioning
confidence: 99%